Comprehensive quality evaluation method of smart meters based on AHP-Critic. Issue 1 (May 2021) - Yuan, Xiangyu; Zhang, Penghe; Li, Ning; Li, Yike; Hou, Yucheng; Xiong, Suqin
Abstract: The quality of smart meters directly affects the stability, security and economy of information gather system and power grid. This paper proposes a comprehensive quality evaluation method of smart meters based on AHP-Critic theory. In this method, firstly, the hierarchy of AHP is established to determine the contents of target layer, rule layer and scheme layer; secondly, the judgment matrix is constructed to calculate the hierarchical single ranking value and carry out consistency test; thirdly, the objective weight of rule layer is calculated by using Critic theory; finally, the comprehensive weight of rule layer is obtained by combining AHP and Critic, and the hierarchical total ranking of target layer to scheme layer is calculated. The experimental analysis takes three types of smart meters as evaluation objects, and the results effectively evaluate the quality of each meter.